2003
DOI: 10.1021/la020881i
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Investigation of the Influence of Cross-Linker Concentration on the Volume Phase Transition of Poly(N-isopropylacrylamide) Colloidal Microgels

Abstract: A series of poly(N-isopropylacrylamide) microgels were prepared, by a surfactant-free emulsion polymerization method, incorporating varying cross-linker concentrations (0.25−30.0% of N,N‘-methylenebisacrylamide). Turbidimetric, light scattering, and differential scanning calorimetric (DSC) analyses of aqueous dispersions of these microgels show that the temperature and the half-width of the overall volume phase transition (VPT) of the colloidal dispersions increase with increasing cross-linker concentration. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
0
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 37 publications
8
69
0
4
Order By: Relevance
“…They observed an overall decrease in phasetransition enthalpy with increase in cross-linker density. [94] In addition to DSC they also used pulsed-gradient spin echo (PGSE) NMR spectroscopy to study the mobility of the solvent in the particle as a function of cross-linker density and observed that the diffusion of solvent is reduced with the increase in the cross-linker density, hence the particles are more rigid at high cross-linker density. Figure 8 depicts the change in relative diffusion coefficient of water in the microgels, measured by PGSE-NMR spectroscopy, for samples with different cross-linker densities.…”
Section: Microgels and Nanogelsmentioning
confidence: 99%
“…They observed an overall decrease in phasetransition enthalpy with increase in cross-linker density. [94] In addition to DSC they also used pulsed-gradient spin echo (PGSE) NMR spectroscopy to study the mobility of the solvent in the particle as a function of cross-linker density and observed that the diffusion of solvent is reduced with the increase in the cross-linker density, hence the particles are more rigid at high cross-linker density. Figure 8 depicts the change in relative diffusion coefficient of water in the microgels, measured by PGSE-NMR spectroscopy, for samples with different cross-linker densities.…”
Section: Microgels and Nanogelsmentioning
confidence: 99%
“…Electrophoresis can be used to measure mobility of a charged microgel within an electric field, enabling estimation of the microgel surface charge density [6]. Differential scanning calorimetry can be used to characterize the critical temperature as well as the magnitude of bulk phase transitions within thermally-responsive microgels [7][8][9]. Rheological analysis can be used to estimate the bulk water content within microgels or study the formation of colloidal crystals and other macroscopic assemblies of concentrated microgel suspensions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…These studies reveal that the PNIPAM gel particles dispersed in water are in a swollen state at room temperature due to hydrogen bonding between solvent water and amide groups, i.e. N -isopropylacrylamide (NIPAM) units and crosslinker methylenebisacrylamide (MBAM) units [21]. We have observed that PNIPAM microgel particles dispersed in water gradually shrank with elevating temperature (≈ 31…”
Section: Introductionmentioning
confidence: 99%